Preemptive flurbiprofen axetil for sleep-pain-inflammation modulation after laparoscopic gynecological surgery: a prospective, parallel-group randomized controlled trial - Huang, Xin; Wei, Wenxin; Leng, Zhihao; Song, Bijia; Fu, Ming; He, Jiangshan; Zhu, Junchao (Frontiers in Pharmacology, 2025)
BackgroundPostoperative pain, inflammation, and sleep disturbances commonly arise after laparoscopic gynecological surgery and are increasingly recognized as interconnected factors that impede recovery and diminish quality of life. Flurbiprofen axetil, classified as a NSAID, is widely used during the perioperative period for pain management. Its potential to modulate inflammatory pathways and nociceptive transmission, thereby enhancing postoperative sleep quality, remains underexplored. Additionally, the optimal timing for NSAID administration—preoperative versus postoperative—remains debated, with limited evidence addressing its impact on sleep outcomes.ObjectivesThis study investigates the impact of preoperative compared to postoperative use of flurbiprofen axetil on pain, systemic inflammatory responses, and particularly the sleep quality in patients undergoing laparoscopic gynecologic operations.MethodsIn this prospective, randomized controlled trial, 98 patients undergoing laparoscopic gynecological surgery were assigned to receive 50 mg of flurbiprofen axetil either 15 min prior to surgery (PreFA group) or at the end of surgery (PostFA group). The primary outcomes assessed included postoperative pain intensity (visual analog scale, VAS), sleep quality (Athens Insomnia Scale, AIS), and systemic inflammatory markers (SII, NLR, and MLR). Outcome data were collected by blinded assessors at predefined time points: preoperatively, 24 h, and 72 h postoperatively.ResultsThe baseline characteristics were similar between groups. The PreFA group demonstrated significantly lower VAS scores for both resting and exertional pain at 24 and 72 h after surgery (P < 0.05). AIS scores were also substantially lower in this group on postoperative days 1 and 3 (P < 0.001 and P = 0.002), reflecting improved sleep quality. Inflammatory markers (SII, NLR, MLR) were elevated postoperatively in both groups but remained significantly lower in the PreFA group (all P < 0.05). Additionally, the incidence of postoperative nausea and vomiting was reduced in the PreFA group.ConclusionPreoperative administration of flurbiprofen axetil not only improved postoperative analgesia and reduced inflammatory responses but also significantly enhanced sleep quality, an essential yet frequently underestimated component of recovery. These findings underscore the broader physiological benefits of preemptive NSAID use and emphasize the importance of timing in analgesic strategies. Incorporating flurbiprofen axetil into preemptive multimodal analgesia protocols could provide a straightforward yet effective approach to optimizing recovery following laparoscopic gynecological surgery.Clinical Trial Registrationclinicaltrials.gov, identifier NCT04611763.